Application of 2-D electrical resistivity imaging, and induced polarization methods for delineating gold mineralization at Felda Chiku 3, Kelantan, Malaysia - Hussein Ahmed Hasan Zaid,; Mohd Hariri Arifin,; Kayode, John Stephen; Mohd Basril Iswadi Basori,; Mohd Rozi Umor,; Suraya Hilmi Hazim,
A geophysical survey has been carried out to assess the distribution of gold minerals at the Felda Chiku 3, Gua Musang district, Kelantan, Peninsular Malaysia. A 2-D geo-electrical resistivity imaging (ERI), combined with Induced Polarization (IP) method, and Oasis Montaj modelling were applied to delineate the potential conductive zones associated with sulphide mineralization. Most Peninsular Malaysia’s gold deposits occur in hydrothermal sulphides as discrete ore formations within the host rocks. A good correlation between the ERI and the IP profiles was observed during the interpretation of the model that successfully identifying the low resistive, and high chargeable sulphide zones, which correspond to the gold mineralization zones. The correlations could be linked to the conductive features at depth ranging from about 25 m - 135 m, trending along N-S directions. The study suggests further geo-electrical investigation to be carried out towards the south-western part of the area as more potential mineralized zones with N-S trends could be found in this region. Further studies would be able to give the extent of the gold deposits in Kelantan and by extension, allow for better informed mineral exploration and drilling operations to mine the gold in the region.